The most accurate technological applications for teaching the English language - Castro Labor, María Elena; Orellana, Rocío Yamileth; Grande, Marta Yecenia (2024)
In the following project, the research team provided a synthesis of the virtual tools and platforms learned during the specialization course “Administración de Ambientes Virtuales para la Enseñanza y Aprendizaje de Idiomas Extrangeros” ("Management of Virtual Environments for Teaching and Learning of Foreign Languages"); thus, teachers know the importance of the most common tools available for online teaching purpose. Furthermore, the complete course was divided into 3 modules which had 8 weeks each. In each module, students learned about different current technological tools and applications which provided students with extensive knowledge about them throughout the course. The first module focused mainly on online education and its applications in teaching the English language, specifically in the virtual teaching approach. Moreover, the second module focused on the theoretical fundaments and the use of technological tools for the teaching-learning of a foreign language in a virtual modality. Additionally, in module three students learned to use at least four web tools for the design of educational materials, and the preparation of other materials such as podcasts, online presentations, interactive images, videos among others. This project was a compilation of the activities carried out during the course with the aim of showing the learning obtained during it. Likewise, the result of each of the activities that were carried out throughout the course is shown through screenshots. Each activity is described according to the acquired knowledge of the student who carried it out. In addition, the students provided a variety of conclusions and recommendation. Key words: Distance Education ; Educational Technology ; E-learning ; Learning Management System ; Synchronous Learning ; Asynchronous Learning ; Technological Tools.